21st Century Skills Oriented Science Learning Worksheets for Elementary Schools - Santiani, Ni Putu Ertha; Parmiti, Desak Putu; Werang, Basilius Redan (Universitas Pendidikan Ganesha, 2024)
The low learning outcomes of science in grade V elementary schools require educators to innovate in developing learning tools. This study aims to develop LKPD oriented toward 21st-century skills that are valid and effective. This research uses the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. This study took the subject of 21st-century skills-oriented LKPD media, while the objects of development research were media content validity, student responses, teacher responses, and media effectiveness. This study utilizes qualitative and quantitative descriptive analysis methods. The data collection methods were observation, interviews, and performance tests to assess student products. The instruments used to collect data were interview guidelines, rating scale sheets, and performance guidelines to assess student products. The results of the media validity test obtained scores from media experts of 0.90 and material experts of 0.92, student responses of 94%, and teacher responses of 98% with very good predicate/qualification. These results align with the study objectives to obtain valid and effective LKPDs. It is concluded that the 21st-century skills-oriented LKPD on science content is declared valid and effective in learning to improve the science learning outcomes of fifth-grade elementary school students.